2013
DOI: 10.1002/pds.3455
|View full text |Cite
|
Sign up to set email alerts
|

Use of QT‐prolonging medications in US emergency departments, 1995–2009

Abstract: Use of QT-prolonging medications is increasing in EDs nationally. A small number of agents account for a large proportion of these visits and may represent an area for targeted screening or monitoring interventions in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
1
11
0
2
Order By: Relevance
“…At hospital admission, the most prescribed QT-prolonging drug classes were diuretics, particularly furosemide, alone or in combination, which is associated with QT-related arrhythmias via its capacity to cause hypokalemia, followed by proton pump inhibitors (pantoprazole, with its ability to trigger hypomagnesemia) and In contrast to other studies [29], we showed the frequent prescription of pantoprazole, the only proton pump inhibitor within the list [2]. This new finding should not be surprising as the AzCERT list is continuously updated [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At hospital admission, the most prescribed QT-prolonging drug classes were diuretics, particularly furosemide, alone or in combination, which is associated with QT-related arrhythmias via its capacity to cause hypokalemia, followed by proton pump inhibitors (pantoprazole, with its ability to trigger hypomagnesemia) and In contrast to other studies [29], we showed the frequent prescription of pantoprazole, the only proton pump inhibitor within the list [2]. This new finding should not be surprising as the AzCERT list is continuously updated [2].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 1464 (1529 total minus 65 dead) patients discharged alive who were taking a QT-prolonging drug alone, 313 (21.4 %) with other QT-prolonging drugs. At discharge, levofloxacin and ciprofloxacin were the antibacterials most prescribed, alone and in combination, although levofloxacin was recently recognized to carry a definite risk of TdP [2,29]. Moreover, haloperidol and domperidone, which both have a definite risk of TdP, were among the most frequently prescribed drugs at discharge, alone and in combination.…”
Section: Discussionmentioning
confidence: 99%
“…12 These findings likely reflect a growing comfort of ED physicians with ondansetron use, which has increased from 0.4% of all ED visits in the US in 1995 to 9.2% in 2009. 33 Although research in other diseases has employed clinical trials to document evidence of efficacy, none have been performed in children with T1DM and intercurrent illness. Our findings point out the need for such research to provide the evidence necessary to justify practice guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Diphenhydramine has been associated with (1) TdP, occasionally during voluntary overdoses [4446]; (2) a strong signal for TdP in the databases from drug regulatory agencies [47]; (3) QTc prolongations during voluntary overdoses [4852], and (4) QTc prolongations in EKGs completed at the emergency room when prescribed by itself or with other drugs that prolong the QTc interval [53]. However, some of these diphenhydramine overdose studies with EKG data, including 126 cases of overdoses with no TdP case [48] and 1 case monitored for several days [50], suggested that diphenhydramine causes tachycardia and this has a major effect on protecting from TdP in situations of QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%